2009
DOI: 10.1136/adc.2008.138875
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal diamorphine for acute sickle cell pain

Abstract: The painful crisis is the commonest acute presentation of sickle cell disease (SCD), yet effective pain control in hospital is often delayed, inadequate and dependent on injected opiates. Intranasal diamorphine (IND) has been used in paediatric emergency departments for management of acute pain associated with fractures, but the analgesic effect is short lived. We evaluated its efficacy and safety when given in combination with intravenous or oral morphine for rapid analgesia for children presenting to our eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Topical lidocaine has been proposed to mitigate the discomfort associated with a few IN medications . Lugo et al were the first in the medical literature to share their anecdotal success with lidocaine prior to IN midazolam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical lidocaine has been proposed to mitigate the discomfort associated with a few IN medications . Lugo et al were the first in the medical literature to share their anecdotal success with lidocaine prior to IN midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Topical lidocaine has been proposed to mitigate the discomfort associated with a few IN medications. 11,17 Lugo et al 12 were the first in the medical literature to share their anecdotal success with lidocaine prior to IN midazolam. In their population of children undergoing upper endoscopy, they theorized that midazolam causes irritation either by pH, its preservative, or the drug itself, and they felt that lidocaine counteracted this discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, administering lidocaine spray prior to administration of INM, as previously suggested by Lugo et al, 18 prevented children from experiencing unpleasant nasal sensations. Based on this experience, lidocaine spray may be used also for preventing nasal discomfort related to other drugs administered by the intranasal route, such as diamorphine recently utilised in the management of acute sickle cell pain 25. All patients achieved an adequate level of sedation throughout each procedure, without requiring additional drugs or additional doses of midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study looked at the efficacy and safety of intranasal diamorphine in pediatric patients, when given in combination with intravenous or oral morphine. The study found rapid improvements in pain scores with no serious side effects, making intranasal diamorphone a potential therapy for acute control of sickle cell pain in the hospital [84].…”
Section: -2009: the Period Of Action And Greater Prospectsmentioning
confidence: 81%